2017
DOI: 10.1177/1076029617739703
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Directed Thrombolysis Versus Standard Anticoagulation for Acute Lower Extremity Deep Vein Thrombosis: A Meta-Analysis of Clinical Trials

Abstract: Standard anticoagulant treatment alone for acute lower extremity deep vein thrombosis (DVT) is ineffective in eliminating thrombus from the deep venous system, with many patients developing postthrombotic syndrome (PTS). Because catheter-directed thrombolysis (CDT) can dissolve the clot, reducing the development of PTS in iliofemoral or femoropopliteal DVT. This meta-analysis compares CDT plus anticoagulation versus standard anticoagulation for acute iliofemoral or femoropopliteal DVT. Ten trials were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
7

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
1
14
0
7
Order By: Relevance
“…Indeed, the heterogeneity of data in many publications regarding endovenous thrombolysis makes even meta-analysis of these outcomes difficult. 8 A further observation is that the rate of PTS in the ATTRACT trial in the PCDT arm is higher than previous publications and, in particular, when compared with that of large volume centres with long experience. The Copenhagen group demonstrated a rate of any PTS of 17% in 109 patients with iliofemoral DVT treated with catheter-directed thrombolysis (CDT) after a median follow up of 71 months.…”
mentioning
confidence: 75%
“…Indeed, the heterogeneity of data in many publications regarding endovenous thrombolysis makes even meta-analysis of these outcomes difficult. 8 A further observation is that the rate of PTS in the ATTRACT trial in the PCDT arm is higher than previous publications and, in particular, when compared with that of large volume centres with long experience. The Copenhagen group demonstrated a rate of any PTS of 17% in 109 patients with iliofemoral DVT treated with catheter-directed thrombolysis (CDT) after a median follow up of 71 months.…”
mentioning
confidence: 75%
“…However, to date, endovascular treatment options for the management of acute iliofemoral DVT remain controversial because of inconclusive study results [16][17][18][19][20]. Indeed, several studies reported results of CDT and PMT in the literature [6][7][8][9][10][11][12][16][17][18][19][20]. The randomized controlled CaVenT trial included 189 patients with acute iliofemoral DVT divided into 2 groups as anticoagulant therapy alone and anticoagulant therapy plus CDT [19].…”
Section: Discussionmentioning
confidence: 99%
“…DVT'nin tedavisinde antikoagülan kullanımı altın standart olmasına rağmen, antikoagülan kullanımının tek başına derin venlerde tam açıklık sağlayamadığı bilinmektedir. 7 Bu nedenle trombolitik ajanın direkt trombüs içine uygulandığı yöntemler son yıllarda popüler hâle gelmiş ve yaygın uygulanır olmuştur. Genellikle anjiyografi ünitelerinde skopi eşliğinde ve USG kılavuzluğunda IV kateter uygulaması gerektiren kateter aracılı tromboliz, farmakomekanik kateter aracılı tromboliz veya venöz anjiyoplasti/stentleme yöntemleri kullanılmaktadır.…”
Section: Discussionunclassified